2021
DOI: 10.1097/spv.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Putative Uropathogen Abundance and Antibiotic Resistance Gene Carriage in Women With Refractory Recurrent Urinary Tract Infection Treated With Fecal Microbiota Transplantation

Abstract: ObjectiveThe aims of this study were to describe the fecal relative abundance of potentially uropathogenic bacteria and to analyze antibiotic resistance genes before and after fecal microbiota transplantation in women with recurrent urinary tract infection (UTI).MethodsShotgun sequencing was performed on fecal samples from 3 donors and 4 women with recurrent UTI who underwent transplantation. Recipient samples were sequenced at baseline and at 4 time points through 6 months postintervention. Relative fecal uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a retrospective study of FMT in patients with rUTI, the bacterial antibiotic susceptibility profile improved after FMT 5 . Comparatively, a recent study of patients having undergone FMT solely for the investigation of its effects on the bacterial profile of patients with rUTI has indicated that uropathogen abundance in these patients’ gut microbiomes is low and that gene carriage in those pathogens found to carry antibiotic resistance persisted at similar levels after FMT 24 . These contradictory findings suggest a persisting lack of clarity regarding FMT’s effects on the urinary microbiome of patients with rUTI.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of FMT in patients with rUTI, the bacterial antibiotic susceptibility profile improved after FMT 5 . Comparatively, a recent study of patients having undergone FMT solely for the investigation of its effects on the bacterial profile of patients with rUTI has indicated that uropathogen abundance in these patients’ gut microbiomes is low and that gene carriage in those pathogens found to carry antibiotic resistance persisted at similar levels after FMT 24 . These contradictory findings suggest a persisting lack of clarity regarding FMT’s effects on the urinary microbiome of patients with rUTI.…”
Section: Discussionmentioning
confidence: 99%